THE URGENCY OF ARRANGEMENT REGARDING ILLICIT ENRICHMENT IN INDONESIA IN ORDER TO ERADICATION OF CORRUPTION CRIMES BY CORPORATIONS - Hamdan Rampadio; Ana Fauzia; Fathul Hamdani (UNISSULA, 2022)
Along with the times, the motives or concept of corruption are increasingly complex and growing, as well as the increasing number of transnational crimes, it makes the world need regulations regarding illicit enrichment in legal products at the level of law to allow the imposition of legal sanctions for these crimes, including Indonesia. The purpose of this study is to provide an overview of the practice of illicit enrichment in Indonesia and its comparison with other countries, as well as an analysis of the urgency of regulating illicit enrichment in Indonesian law as one of the most important norms in efforts to eradicate corruption in Indonesia. In this study, the method used is normative juridical using a statutory, conceptual and case approach. From the results of the study, an idea that is presented in efforts to develop and reform law in Indonesia, namely in the context of eradicating corruption. This idea is discussed in more depth through a number of concrete cases that have been processed in Indonesia which shows that if we have illicit enrichment norms, the handling of these cases will be maximized. Through this regulation related to illicit enrichment, of course, it can prevent public officials (corporations) from committing corruption, minimizing initiatives to do business or other activities that are full of conflicts of interest (with their positions).